Big or Small, Profitable or Not: What Do Investors Really Respond To? - Busono, Aulia (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2025)
This study aims to understand what factors influence investor responses to companies. Using a mixed methods approach, it analyzes quantitative data from 50 companies listed on the Indonesia Stock Exchange and conducts qualitative interviews with investors and financial analysts. The results show that profitability, measured by Return on Assets (ROA), is the strongest financial factor in attracting investor interest. Company size and institutional ownership also have effects, but their impact is smaller. The study also found that investor emotions, such as trust, hope, and fear, play a big role in investment decisions. Companies that show good financial performance, build trust, and share a strong vision for the future are more attractive to investors. This study contributes to the literature by combining financial metrics and investor psychology to better understand what drives investor behavior. It offers practical insights for companies on strengthening investor relations by focusing on financial performance and emotional factors such as trust and future vision.